Tearing the veil of privacy law: An experiment on chilling effects and the right to be forgotten - Yoan Hermstrüwer; Stephan Dickert (Max Planck Institute for Research on Collective Goods, 2013)
Privacy law relies on the argument that consent does not entail any relevant impediments for the liberty of the consenting individual. Challenging this argument, we experimentally investigate whether consent to the publication of personal information in cyberspace entails self-coercion on a social norm level. Our results suggest that the monetary benefits from consent constitute a price that people are willing to accept for increased compliance with social norms. Providing people with a prior consent option is sufficient to generate chilling effects (i.e., a reduction of norm-deviant behavior). However, nudging people towards potential publicity does not increase the value they place on privacy. We also test how the default design of the right to deletion of personal information (right to be forgotten) affects chilling effects and privacy valuations. Surprisingly, the right to be forgotten does not reduce chilling effects. Moreover, individuals tend to stick with the status quo of permanent information storage.
Keywords: C93; C91; A13; D03; K29; 330; Social Norms; Nudges; Behavioral Law and Economics of Privacy; Consent; Right to Be Forgotten; Dictator Games